Effects of Dehydration on Cytoskeleton - Zhu Kai; Dong Yang; Wang Yabo; Xie Yanqi (Zhileng xuebao)
Drastic changes in the surrounding environment have a certain effect on the inner regions of cells. In this study, the morphology of microfilaments in the cytoskeleton during dehydration is studied by Coomassie brilliant blue staining and digital image processing. By analyzing the gray-scale kurtosis of the processed image, it is observed that as the dehydration process progresses, the gray-scale image shows a decrease in dispersion, the skeleton morphology is looser, and a series of morphological changes are accompanied by depolymerization. Through quantitative calculation of the characteristic parameters of the image, it is inferred that the final relative rate of change of the skeleton under a continuous vacuum environment is 32.7%, and that under a continuous low temperature environment is 59%. Finally, a study on the degree of cell deformation shows that the dehydration process has a more significant effect on the cytoskeleton.